1998
DOI: 10.1086/515613
|View full text |Cite
|
Sign up to set email alerts
|

First Human Trial of a DNA-Based Vaccine for Treatment of Human Immunodeficiency Virus Type 1 Infection: Safety and Host Response

Abstract: A DNA-based vaccine containing human immunodeficiency virus type 1 (HIV-1) env and rev genes was tested for safety and host immune response in 15 asymptomatic HIV-infected patients who were not using antiviral drugs and who had CD4+ lymphocyte counts of > or = 500 per microliter of blood. Successive groups received three doses of vaccine (30, 100, or 300 microg) at 10-week intervals in a dose-escalation trial. Vaccine administration induced no local or systemic reactions, and no laboratory abnormalities were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
297
2
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 576 publications
(312 citation statements)
references
References 44 publications
10
297
2
3
Order By: Relevance
“…Unfortunately, clinical trials have shown the limited efficacy of DNA vaccination in human volunteers, which necessitates the identification of technologies that can enhance DNA vaccines [20,21]. Among the strategies being evaluated to increase the efficiency of DNA vaccination is the use of non-viral vectors to deliver the DNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, clinical trials have shown the limited efficacy of DNA vaccination in human volunteers, which necessitates the identification of technologies that can enhance DNA vaccines [20,21]. Among the strategies being evaluated to increase the efficiency of DNA vaccination is the use of non-viral vectors to deliver the DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous scientific publications have reported the effectiveness of DNA vaccines in providing potent immune responses or protective immunity against viruses, bacteria and parasites in several species including human volunteers [19][20][21]. DNA vaccination has become an accepted method in the research community, and is now being tested on humans.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we initiated the Âźrst human trials for DNA vaccines. The preliminary results of these studies reveal immune enhancement and no clinical or laboratory adverse e ects measured in three dosage groups (30, 100, 300 mg) (RR MacGregor, 1998).…”
Section: Discussionmentioning
confidence: 81%
“…Although DNA vaccines have thus far performed poorly in clinical trials, [23][24][25] their efficacy in preclinical small rodent models against infectious diseases or cancers has been impressive. 26,27,[4][5][6] DNA vaccines are easy to construct and they induce a full spectrum of immune responses including CD8 + T cells, 26 which have been implicated to play a major role in tumor cell eradication.…”
Section: Discussionmentioning
confidence: 99%